A review of the approaches to predict the ease of swallowing and post-swallow residues. (April 2019) - Marconati, M.; Engmann, J.; Burbidge, A.S.; Mathieu, V.; Souchon, I.; Ramaioli, M.
Abstract: Background: Swallowing is a complex physiological process transporting food from the mouth into the esophagus. Understanding how food properties condition flow, ease of swallowing and amount of post-swallow residues can support the design and development of novel products with improved texture and swallow-ability. Diagnostics allowed visualizing directly the effect of bolus consistency on flow, but complementary approaches are needed to speed up the pace of product innovation. Scope and approach: This review summarizes the state of the art with respect to the in vitro and in silico approaches to predict the ease of swallowing, with an overview of the oral, pharyngeal and esophageal swallowing. Physical and computational models are discussed and compared, highlighting capabilities and limitations. Key findings and conclusions: In vitro and in silico experiments represent attractive complements to the in vivo investigations because they allow varying parameters independently, which is key to understand the effect of different food and drink properties and to adapting them to different needs. Two motor control strategies are commonly used, namely imposing displacements or stresses. These models have helped clarifying the role of bolus rheology in the oral phase of swallowing and the importance of salivary coating in the pharyngeal bolus flow. Few areas of improvements were identified: the use of more realistic geometries and mechanical properties representing the relevant tissues, of lubrication boundary conditions and of a wider variety of food boli. Further clinical studies should also focus on identifying the most realistic motor control strategy to mimic human swallowing. Highlights: In vitro and in silico models to predict the ease of swallowing are discussed. The relevant physiology, bolus and tissue properties are introduced. The oral, pharyngeal and esophageal phases of swallowing are considered. Different swallow motor control scenarios are discussed. Limitations of existing models and future research opporunities are reviewed.